The 1956 Hungarian Revolution : Hungarian and Canadian perspectives - Adam, Christopher (International Canadian studies series., 2010)
In October 1956, a spontaneous uprising took Hungarian Communist authorities by surprise, prompting Soviet authorities to invade the country. After a few days of violent fighting, the revolt was crushed. This collection focuses on the impact of the revolution in Hungary, in Canada, and around the world.